2015
DOI: 10.1007/s10551-015-2635-z
|View full text |Cite
|
Sign up to set email alerts
|

Circles of Ethics: The Impact of Proximity on Moral Reasoning

Abstract: We report the results of an experiment designed to determine the effects of psychological proximityproxied by awareness of pain (empathy) and friendshipon moral reasoning. Our study tests the hypotheses that a moral agent's emphasis on justice decreases with proximity, while his/her emphasis on care increases. Our study further examines how personality, gender, and managerial status affect the importance of care and justice in moral reasoning. We find support for the main hypotheses. We also find that care sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…In addition, the current research is interested in whether moral foundations directly or indirectly influence consumer boycott behaviors. Some researchers suggest that consumer boycott participation may not be directly affected by moral values and that their behaviors are more driven by negative appraisals of the company’s business decisions/practices and the anger evoked as a result of such appraisals (Lim, 2017; Wildermuth, De Mello e Souza, & Kozitza, 2017). As such, we identified two factors that potentially mediate the impact of moral foundations on boycott behavior.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the current research is interested in whether moral foundations directly or indirectly influence consumer boycott behaviors. Some researchers suggest that consumer boycott participation may not be directly affected by moral values and that their behaviors are more driven by negative appraisals of the company’s business decisions/practices and the anger evoked as a result of such appraisals (Lim, 2017; Wildermuth, De Mello e Souza, & Kozitza, 2017). As such, we identified two factors that potentially mediate the impact of moral foundations on boycott behavior.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As such, we identified two factors that potentially mediate the impact of moral foundations on boycott behavior. Blame attribution and anger are the two factors that potentially mediate the impact of moral foundations on boycott intentions, when consumers are exposed to a crisis caused by a supplier’s immoral business practices and subsequent tragic human loss (Wildermuth et al, 2017; Zourrig, Chebat, & Toffoli, 2009). In the following sections, we review the literature that explains the relationship between moral values and the two factors.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Previous studies suggest that factors such as a shared background and interests can influence business negotiations (Jones, 1991; Wildermuth et al , 2017). Cognitive proximity – sharing a common knowledge base and belonging to the same community of practice – facilitates efficient communication and improves mutual understanding in new or complex settings (Nooteboom, 1999; Boschma, 2005; Mattes, 2012).…”
Section: Background and Hypothesis Developmentmentioning
confidence: 99%
“…Psychological proximity includes a level of commitment to others in which an actor feels close on an affective level, in a way similar to one’s commitment to family and close friends. The relationship between psychological proximity and care is supported empirically by Wildermuth et al . (2017) who found that care and moral reasoning strengthens with closeness and weakens with distance.…”
Section: A Call To Empathic Carementioning
confidence: 84%